STAFF MOTIVATION AS A TOOL OF EFFECTIVE PERSONNEL POLICY OF THE ORGANIZATION - O. S. Suvalov; T. V. Suvalova (Вестник университета)
The aim of the study is to analyse the personnel motivation and incentive system used in Russian companies. The relevance of evaluating the labour of employees has been substantiated in the article, the rating system, KPI, grades for determining the plug of official salaries has been considered. The features of the motivation psychology have been highlighted. The importance of maintaining a balance of interests of employees and company management in the formation of the incentive system has been justified. Attention on the formation of reward systems has been focused. The practice of creating a system of motivation and stimulation of labour has been considered. The data of an all-Russian study conducted by Kelly Service have been presented. The effectiveness of the application of various types of social package has been noted. The most popular types of benefits,on the basis of which several social packages can be compiled, have been described. The principles that contribute to improving efficiency of the functioning of the entire incentive system have been considered.